Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/ijerph192215139
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanisms of Parental Burnout Affecting Adolescents’ Problem Behavior

Abstract: Parental burnout refers to the feelings of extreme exhaustion that many parents experience due to parenting. Although parental burnout has received considerable interest from researchers, the effects and mechanisms of parental burnout on adolescents’ physical and psychological development remain largely unknown. This study investigated the relationship between parental burnout and adolescents’ problem behaviors in Chinese families. We explored the mediating roles of family function, parental psychological aggr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 54 publications
3
11
0
Order By: Relevance
“…As opposed to the child’s internalizing behavior, which was weakly correlated with parental burnout ( r = 0.12), the size of the bivariate correlation coefficient between the child’s externalizing behavior and parental burnout was moderate ( r = 0.32). Our results thus replicate those of the authors of [ 12 , 27 , 28 ], who observed correlation coefficients between parental burnout and child internalizing/externalizing problems ranging from 0.12 to 0.24 in their respective samples. Additionally, as in Chen and his colleagues’ study [ 12 ], we observed that the association between parental burnout and child externalizing behavior was statistically stronger than the association between parental burnout and child internalizing behavior, z = −2.91, p < 0.01.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…As opposed to the child’s internalizing behavior, which was weakly correlated with parental burnout ( r = 0.12), the size of the bivariate correlation coefficient between the child’s externalizing behavior and parental burnout was moderate ( r = 0.32). Our results thus replicate those of the authors of [ 12 , 27 , 28 ], who observed correlation coefficients between parental burnout and child internalizing/externalizing problems ranging from 0.12 to 0.24 in their respective samples. Additionally, as in Chen and his colleagues’ study [ 12 ], we observed that the association between parental burnout and child externalizing behavior was statistically stronger than the association between parental burnout and child internalizing behavior, z = −2.91, p < 0.01.…”
Section: Resultssupporting
confidence: 90%
“…Of the three categories of parental burnout correlates outlined above, the last one (that relates to the child’s characteristics or behavior) has received much less scholarly attention thus far. In the studies of the few authors who have addressed this issue, we observe associations between parental burnout and child externalizing and internalizing behaviors [ 12 , 18 , 27 , 28 ]. However, because these studies were conducted in specific contexts (i.e., in Chinese settings with adolescents for the first, third and fourth studies) and under specific conditions (i.e., in the COVID-19 pandemic for Kerr’s study with only five items from the Parental Burnout Assessment Scale (PBA, [ 29 ]) and using a subset of children’s health questions from the National Survey of Children’s Health (Child and Adolescent Health Measurement Initiative, 2018)), these associations need to be replicated in different age groups and in different cultural contexts both with the 23 items that comprise the Parental Burnout Assessment Scale (PBA, [ 29 ]) and with a measure specifically intended to assess the child’s internalizing and externalizing behaviors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the theoretical framework proposed by Lui et al [ 17 ] explains how the family and personal factors of teenagers interact and have an impact on parents’ parenting burnout. Yuan et al [ 18 ] believe that adolescents’ difficult behavior plays an important role in the collaborative parenting conflict and parenting burnout. They further found that adolescents’ difficult behaviors and family function are widely regarded as the main individual factors affecting parenting burnout in the literature, and family function in family factors has exerted different influences and functions on collaborative parenting conflict, adolescents’ difficult behavior and parenting burnout.…”
Section: Introductionmentioning
confidence: 99%
“…According to family systems theory, the family is a dynamic and interactive system, and family members are interdependent and influence each other (Cox & Paley, 2003). Burned-out parents lack enthusiasm for parenting, have no energy to provide other support beyond basic care, and are more likely to engage in negative parenting practices, all of which considerably increase children's risk of negative behaviors, such as arguing a lot, threatening people, internalized problem behavior and externalized problem behavior (Chen et al, 2022; Yuan et al, 2022). Additionally, a prior study revealed that parenting stress increases children's risk for negative behavior (Mash & Johnston, 1990).…”
Section: Introductionmentioning
confidence: 99%